Compensatory beliefs in the internet gratification behavior: A study of game-based assessment - Yin, Bin; Shen, Yong (Frontiers in Public Health, 2023)
Internet gratification behaviors (IGB) may lead to sub-optimal performance in schools and workplace as well as mental health problems such as Internet addiction. The present research examines this phenomenon, focusing on the compensatory belief (CB)—a belief that the negative impact of a certain behavior can be compensated or neutralized by another positive behavior—as a potential psychological mechanism for IGB. An interactive-narrative-style game-based assessment was designed and responses from a random-sampled population of 1,298 participants including college students and organizational employees were collected online. It was found that around 40% of college students and organizational employees would activate some kind of compensatory beliefs when facing with the internet temptation. Those who failed to perform compensatory behaviors afterwards were more likely to regret than those who were able to perform them, which was consistent with the prediction of the CB theory. This study expands the applicability of the CB theory to the field of internet addiction, enriches the understanding of the psychological mechanisms of internet addiction, and suggests that the interactive-narrative-style game-based assessment may be a practical method to study the CB.